Chemical vapor transport growth of bulk black phosphorus single crystals. Issue 15 (14th July 2020) - Khurram, Muhammad; Sun, Zhaojian; Zhang, Ziming; Yan, Qingfeng
Abstract : Recent progress in growth of bulk black phosphorus single crystal by CVT method has been briefly reviewed with the emphasis on reaction system, nucleation and growth mechanism as well as advancement in growth of doped BP bulk single crystal. Abstract : Phosphorene, which is designated as a monolayer or a few-layer of orthorhombic black phosphorus (BP), has emerged as a new promising member of the two-dimensional material family. A plethora of exciting applications of phosphorene have been reported based on its intriguing properties. Unfortunately, due to the lack of reliable methods for the direct synthesis of highly crystalline phosphorene, bulk BP single crystals have been the sole precursor to achieve high-quality phosphorene. A chemical vapor transport (CVT) reaction method has been deemed the most successful method for the growth of bulk BP single crystals. Herein, recent progress in the controlled growth of bulk BP single crystals by the CVT reaction is briefly reviewed. The emphasis is focused on the reaction system, nucleation and growth mechanism of the CVT synthesis of bulk BP crystals as well as the recent development in the growth of doped and substituted BP single crystals by the CVT reaction method. The challenges and perspectives ahead of the CVT growth of BP crystals are also pointed out.